Measurements of aircraft wake vortices in ground proximity within an atmospheric boundary layer wind tunnel - Fonti, Elio (Cranfield University, 2010)
The vortex wake characteristics of aircraft during landing and take-off are of interest in connection with both the safety of following aircraft penetrating the vortex and the dispersion of engine exhaust plumes. A series of measurements were carried out in an Atmospheric Boundary Layer Wind Tunnel (ABLWT) to identify and characterise both the mean and turbulent flow field of a pair of wake vortices in ground proximity. Cont/d.